2021
DOI: 10.21608/ejhm.2021.209979
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Dexmedetomidine Versus Magnesium Sulphate on The Adequacy of Hypotensive Anesthesia and Post-Operative Recovery for Patients Undergoing Endoscopic Transnasal Transsphenoidal Pituitary Tumor Resection

Abstract: Background: Perioperative use of magnesium sulfate (MgSO4), dexmedetomidine, have been tried in order to provide beneficial clinical effects during general anesthesia (GA). However, few literature discussed it with varying results. Several clinical researches have showed that usage of MgSO4 infusion was associated with a reduction in anesthetic requirement and postsurgical analgesic consumption during GA.Objective: This study aimed to assess the pharmacologic effects of the use of dexmedetomidine and MgSO4 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The sympatholytic properties of dexmedetomidine could have blunted the response to noxious stimuli during various surgical stages, resulting in a significantly reduced requirement for anesthetics. [12,20,35,36] Our findings align with the previous studies involving intravenous dexmedetomidine in TNTSS, leading to early emergence and extubation. [7,12] In our study, patients in the dexmedetomidine groups had optimal surgical fields, with a substantial percentage of patients having excellent Formmers grades.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The sympatholytic properties of dexmedetomidine could have blunted the response to noxious stimuli during various surgical stages, resulting in a significantly reduced requirement for anesthetics. [12,20,35,36] Our findings align with the previous studies involving intravenous dexmedetomidine in TNTSS, leading to early emergence and extubation. [7,12] In our study, patients in the dexmedetomidine groups had optimal surgical fields, with a substantial percentage of patients having excellent Formmers grades.…”
Section: Discussionsupporting
confidence: 90%
“…Dexmedetomidine’s ability to attenuate stress-induced hypertension also aided in minimizing surgical field bleeding, resulting in better operating conditions. [ 1 , 18 , 31 , 36 ] The use of intravenous dexmedetomidine in TNTSS has been associated with hypotension and bradycardia, necessitating the use of atropine in one study. [ 35 ] In addition, another study reported prolonged hypotension for up to 30 min following administering an intravenous dexmedetomidine loading dose before anesthesia induction.…”
Section: Discussionmentioning
confidence: 99%